COACHING CLINIC CABANG OLAHRAGA PETANQUE - Ridlo, Azi Fais; Iskandar, Tatang; Alzamora, Ilyas (DEVOSI, 2021)
Petanque, is a sport (sports) originating from France. In Indonesia, petanque is a new sport. The purpose of this study was to introduce pentaque sports to SD/MI sports teachers in the District of Rawamerta. The method used in this community service is socialization and coaching regarding the sport of pentanque. The result of this activity is an understanding of the petanque sport for SD/MI sports teachers throughout the District of Rawamerta so that they can carry out guidance and practice well.